Sanctions in the face of crowd riots in sports stadiums Jordanian legal football stadiums as a model - A social study – - Al-Marri, Rashid Saleh Rashid (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the legal penalties in the face of crowd riots in sports stadiums, Jordanian football stadiums as a model - A social study - and to use the descriptive analytical approach as it is the most appropriate to achieve the objectives of this study. The psychometric characteristics (honesty and stability) were extracted from (218) male and female students, and the results of the study indicated that the legal penalties in the face of crowd riots in sports stadiums - Jordanian football stadiums as a model, came at a high level and there were no statistically significant differences in The study sample members’ estimates of legal penalties in the face of crowd riots in sports stadiums - Jordanian football stadiums as a model due to demographic variables (gender, educational qualification, and age). The study recommended - adopting a body that is responsible at all levels for developing fair play (rewards and prizes) It is also concerned with eliminating the manifestations of sports violence.